PENGUKURAN KEPUASAN KONSUMEN PADA KUALITAS PELAYANAN CUSTOMER SERVICE BERBASIS WEB - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2012)
Telecommunications services activities to be very important, because it is one business that provides a range of facilities that can be used by consumers. This is because the higher level of competition, the level of complexity of care resulted in telecommunications services activities need to be managed professionally. The purpose is to measure customer satisfaction on service quality customer service which provide fast, precise and accurately related to service quality customer service, via the website. Measuring service quality customer service consisting of: five (5) Physical appearance factor (Tangible), Reliability (Reliability), response (Responsiveness), Assurance (Assurance) and Empathy (Empathy) to customer satisfaction. In research there are 2 (two) variables are represented by the letters X and Y, where X is the level of performance that gives satisfaction and customer service performance Y is the level of interest / expectations of customer service. Keywords: customer service, PHP, MySql